(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
De Albanensium seu Græcorum peculiari cura habenda. The religious condition of the Italo-Albanians in Calabria during the post-Tridentine age. Historical and legal outlines Abstract: The invasion of Albania by the Turks in 1478 forced many Albanians to emigrate in the Kingdom of Naples and, in particular, in the Calabrian provinces. These Albanian refugees continued to speak their language and most of all to profess the Catholic religion, but according to the Byzantine rite. The liturgical and doctrinal diversity of this rite led, over the years, Calabrian bishops and priests following the Roman rite to be wary and suspicious towards these canonical practices. Nevertheless, the Holy See was generally benevolent towards the Italo-Albanian Catholic Church allowing the devotes the free exercise of religious practice, protecting diversity and encouraging the education of clerics, by enacting a series of important measures over the Centuries. This paper aims to focus, from a legal-historical perspective, the events concerning the Byzantine rite in Calabria between the 16th and the 18th Centuries, through the analysis of the decrees of some diocesan synods and some of the most important papal measures that allowed the Albanians of Calabria (arbëreshë) to resist the attempts of “Latinization” and at the same time to confirm, despite the diversity, their belonging to the Catholic Church. SOMMARIO: 1. Una premessa - 2. Gli albanesi di rito greco nella Calabria post-tridentina fra sospetti di eterodossia e tentativi di latinizzazione: le disposizioni di alcuni sinodi diocesani - 3. I Pontefici di fronte alla ‘questione’ degli italo-albanesi: dal XVI Secolo alla fondazione del Collegio Corsini.